Formation, stability and in vitro digestibility of nanoemulsions stabilized by high-pressure homogenized lentil proteins isolate. (April 2018) - Primozic, Maja; Duchek, Akaysha; Nickerson, Michael; Ghosh, Supratim
Abstract: Proteins from pulses such as lentil are seen as an important plant-based alternative to animal proteins in the food and beverage industry. In this research physically modified (homogenized at 5000 psi and 15, 000 psi) lentil protein isolate (LPI) solutions (1–2 wt%) were examined as an emulsifier in stabilizing 5 wt% oil-in-water nanoemulsions. High-pressure homogenization was found to significantly decrease LPI particle size distribution, surface hydrophobicity and the interfacial storage moduli relative to the unmodified LPI. However interfacial tension was not affected. No difference in physicochemical properties was observed between the modified LPI solutions prepared at different pressures. All nanoemulsions prepared with modified and unmodified LPI showed droplet flocculation and LPI aggregation, which was increased with protein concentration. Although both the droplet size and instability indices of the modified protein nanoemulsions measured under accelerated gravitation increased after 28 days, they were still better than the unmodified LPI nanoemulsions. In vitro digestion of the nanoemulsions showed significantly higher lipid digestibility for the modified LPI, which was ascribed to the higher interfacial area of smaller droplets and weaker interfacial moduli of modified LPI-stabilized interfaces compared to those with unmodified LPI. Physical modification of LPI by high-pressure homogenization prior to emulsification could be a novel way to utilize pulse proteins in the formation and stabilization of nanoemulsions and improved digestibility under gastrointestinal conditions. Graphical abstract: Image 1 Highlights: Lentil protein isolate was modified by high-pressure homogenization. Nanoemulsion prepared with modified lentil proteins were more stable. Protein modification decreased particle size and increased solubility. Interfacial modulus of modified protein was lower compared to the unmodified one. Lipid digestibility was higher for nanoemulsions stabilized with modified proteins.